B-cell maturation antigen-specific chimeric antigen receptor T cells for multiple myeloma: clinical experience and future perspectives - Sellner, Leopold; Fan, Fuli; Giesen, Nicola; Schubert, Maria-Luisa; Goldschmidt, Hartmut; Müller-Tidow, Carsten; Dreger, Peter; Raab, Marc-Steffen; Schmitt, Michael (International journal of cancer, 2020)
Despite major advances in the treatment of multiple myeloma (MM), it remains a largely incurable disease with long-term control often dependent on continuous therapy. More effective, better tolerated treatments are therefore required to achieve durable remissions and to improve the quality of life of MM patients.
First published: 09 April 2020
Gesehen am 05.01.2022